PENGARUH PEMBERIAN AMELIORAN TERHADAP BEBERAPA SIFAT KIMIA TANAH GAMBUT DAN PERTUMBUHAN VEGETATIF TANAMAN KEDELAI (Glylicine max, L. Merril) - Nurhayati - (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbstractThis research was arranged in Randomized bloc Design with thirteen treatments and two replicatin consist of control (A0), calcify dolomit (A1), sea mud (A2), calcify dolomit + sea mud (A3), Bradyrhizobium (A4), MOS (A5), peat soil isolat mikoriza (A6), mineral soil isolat mikoriza (A7), Bradyrhizobium +MOS (A8), peat soi isolat mikoriza+mos (A9), mineral soil isolat mikoriza+MOS (10), Bradyrhizobium +MOS+ peat soil isolat mikoriza (A11), Bradyrhizobium +MOS+ mineral soil isolat mikoriza (A12). Variable which to know is pH, DHL, C-organik, C/N, soil nitrogen, soil available P, high of crop at 5 weeks after planting, stem diameter 5 weeks after planting, dry leaf weight, and dry root weigh. Analysis variable with excel program, continue with Duncan Multiple Range Test (DMRT), and corelation coeffient analysis with excel program. The result of this research that giving some material repair soil (calcify dolomit, sea mud, and some biofertilizers) having an effect very sigficant to increase pH, and increase high of crop 5 weeks after planting, and having an effect significant to decrease of DHL, but not having an effect significant to C-organik, C/N, soil nitrogen, soil available P, stem diameter 5 weeks after planting, dry leaf weight, and dry root weigh.Key words : Amelioran, peat soil, calcify dolomit, sea mud, Bradyrhizobium, MOS, mikoriza.